STRATEGI MISI SADRACH SUATU KAJIAN YANG BERSIFAT SOSIO HISTORIS - Silas Sariman (Sekolah Tinggi Theologia Abdiel, 2019)
This writing is to explore the strategy of Christian mission of Kyai Sadrach. Sadrach was a Javanese who proclaimed the Gospel by the cultural approaches. Sadrach could spread the Gospel effectively and his cultural approaches were accepted by the Javanese people at the time. The writer mentions that Sadrach’s mission was the Christian mission that reveals God’s glory. To achieve the aim in explaining the strategy of Sadrach’s mission, the writer talks about the life of Sadrach and his spiritual journey. The Church needs to learn from the strategy of Sadrah’s mission in order for her to proclaim the Gospel contextually.